2021
DOI: 10.26740/lenterabio.v10n1.p106-114
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring Kualitas Perairan Pesisir Pantai Lembung, Pamekasan Menggunakan Bioindikator Fitoplankton

Abstract: Pesisir adalah transisi antara daratan dan lautan yang membentuk ekosistem yang beragam dan produktif. Perairan pesisir memiliki fungsi yang penting karena menjadi habitat beragam organisme, sekaligus rentan mengalami degradasi akibat masuknya polutan dari daratan. Kualitas perairan pesisir dapat diketahui dengan biomonitoring menggunakan fitoplankton. Penelitian ini bertujuan untuk mengetahui kualitas perairan pesisir pantai Lembung, Pamekasan Madura berdasarkan indeks-indeks biologis fitoplankton, fisik-kimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…However, the number of families based on the MZB collection (Table 1) is almost the same as that reported in the publication. The same report also found that the 38 bivalves in Modung Beach bivalves that belong to 15 families, namely Arcidae, Cardiidae, Corbiculidae, Mactridae, Mytilidae, Ostreidae, Pectenidae, Pharidae, Propeamussiidae, Psammobidae, Pinnidae, Solenidae, Tellinidae, Veneridae, and Laternulidae [8]. Another study also reported several families similar to those collected at MZB, for example, Arcidae, Veneridae, Pinnidae, Ostreidae, Isognomonidae, and Mytilidae [5].…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…However, the number of families based on the MZB collection (Table 1) is almost the same as that reported in the publication. The same report also found that the 38 bivalves in Modung Beach bivalves that belong to 15 families, namely Arcidae, Cardiidae, Corbiculidae, Mactridae, Mytilidae, Ostreidae, Pectenidae, Pharidae, Propeamussiidae, Psammobidae, Pinnidae, Solenidae, Tellinidae, Veneridae, and Laternulidae [8]. Another study also reported several families similar to those collected at MZB, for example, Arcidae, Veneridae, Pinnidae, Ostreidae, Isognomonidae, and Mytilidae [5].…”
Section: Discussionmentioning
confidence: 67%
“…Based on the MZB collection, it is known that there were 36 species of bivalves originating from Madura Island. The species richness of bivalves in Madura Island based on the MZB collection is less than that reported in scientific publications in this area, for example, a previous report showed that there were 38 species of bivalves from Modung Beach [8]. This is presumably because the specimen collection came from individual grants instead of the result of a survey visit, as was done at Kepulauan Seribu [11].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Di Pangandaran, Jawa Barat, ditemukan perubahan kualitas dan produktivitas perairan tawar, mangrove, dan estuari yang terjadi antara musim (Nurdiana et al, 2020). Pola yang sama juga ditemukan dari biomonitoring kualitas perairan pesisir Pantai Lembung, Pamekasan, menggunakan bioindikator fitoplankton (Amin & Purnomo, 2021). Pembahasan lebih lanjut mengenai fitoplankton disajikan di subbab berikutnya.…”
Section: B Perubahan Iklimunclassified